Use of Massive Online Open Courses (MOOCs) model in virtual education development in first macro-region universities of medical sciences in countrywide territorial planning - Ensieh Pouladi; Maryam Taghvaee Yazdi; Mohammad Salehi; Siavash Moradi (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Massive online open cources (MOOCs) are a new chapter in the topic of teaching-learning in higher education, which have been able to acquire a significant and valuable position in higher education and prestigious universities worldwide in line with the advancement of technology. The present study was conducted pursuing the goal to investigating the effect of use of MOOCs in the development of virtual education in universities of medical sciences in the first macro-region of countrywide territorial planning.MATERIALS AND METHODS: This research is based on a mixed method and practical in terms of purpose, and it was carried out in 2021 and 2022 in first macro-region of countrywide regional planning Medical Sciences Universities. The data of the qualitative section were converted into a questionnaire using the method of qualitative content analysis in a purposeful and semi-structured interview with 24 experts in the field of virtual education who had sufficient experience in the field of MOOC courses. The statistical population of the quantitative section is 1938 faculty members of the first macro-region of countrywide regional planning, of which 324 were selected by stratified random sampling. Its validity was calculated by Lawshe and Waltz-Bausell method by R software, and the reliability was calculated using Cronbach's alpha method with SPSS-21.RESULTS: Universities are facing challenges in structural, managerial, cultural, social, technological, and evaluation dimensions, and the current situation of using MOOCs in them is not appropriate.CONCLUSION: Besides, the analysis of the optimal situation of using MOOCs in these universities indicates that technological, structural, managerial, evaluation, educational, and personal dimensions are the most important in the effect of using MOOCs on the development of virtual education.